1992
DOI: 10.1017/s0022215100118468
|View full text |Cite
|
Sign up to set email alerts
|

Middle ear effusion: An orthodontic perspective

Abstract: Deviations in facial form are discussed. On the basis of previously published hypotheses, it is suggested that oropharyngeal development may be influenced by the posture, and function of the tongue, lips, and jaws. Attention is drawn to the relationship between a firm tongue to palate swallow, and the pump action of the palatine aponeurosis, which it is suggested is necessary for the aeration of the Eustachian tube. The pump action appears to be reduced in long faced adenoidal children, but clinical evidence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Mew and Meredith [18] suggested that oropharyngeal development may be influenced by the posture, and function of the tongue, lips, and jaws. Firm tongue to palate swallow is related to the pump action of the palatine aponeurosis, which it is suggested is necessary for the aeration of the eustachian tube.…”
Section: Discussionmentioning
confidence: 99%
“…Mew and Meredith [18] suggested that oropharyngeal development may be influenced by the posture, and function of the tongue, lips, and jaws. Firm tongue to palate swallow is related to the pump action of the palatine aponeurosis, which it is suggested is necessary for the aeration of the eustachian tube.…”
Section: Discussionmentioning
confidence: 99%
“…A firm tongue-to-palate swallow, which is seen in breastfeeding, is suggested as necessary for the aeration of the eustachian tube [13]. Pressure readings taken during feeding with standard nonvented and undervented bottles have revealed that negative intratympanic pressure is generated in the infant due to the transmission of negative pressure from the bottle to the middle ear.…”
Section: Breastfeeding and Otitis Mediamentioning
confidence: 99%
“…They acknowledge that orthodontic palatal expansion allows or enables the mandible to be positioned or postured forward, which increases oral muscle tone. This, together with firmer contractions of the tongue and facial muscles when swallowing, may provide advantages for tubal function [61][62][63].…”
Section: Interdental Tongue Positioning and Dental Occlusionmentioning
confidence: 99%
“…In the past, such conditions were thought to be associated with poor skeletal growth of genetic origin. However, recent developments would suggest that these are deviations from normal growth, which could be influenced with some predictability [61].…”
Section: Sniffingmentioning
confidence: 99%